A method for forming a platinum group noble metal catalytic layer on the surface of a nickel textile mesh
By forming the method of forming a platinum precious metal catalytic layer on the surface of the nickel textile network, the problem of uneven active location distribution and stability challenges of precious metal load catalysts in catalytic reactions is solved. Catalytic performance and electrode corrosion resistance.
Patent Information
- Application Number
- CN202411398508.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-09
AI Technical Summary
There are problems of uneven distribution of active sites, inactivation of active sites in precious metals and stability challenges in existing precious metals supported catalysts.
By forming a platinum group precious metal catalytic layer on the surface of the nickel textile mesh, the nickel textile mesh is first pretreated to activate the surface, and then the surface of the nickel textile mesh is wrapped with a film structure prepared by calcium alginate and polyaspartic acid, and then passed through Sulfur-modified carbon-nitrogen particles are mixed with platinum-group noble metal solid particles, and plasma spraying technology is used to form a catalytic layer.
It improves the adhesion and stability of the catalytic layer, enhances the dispersion and catalytic performance of the catalyst, extends the service life of the catalytic layer, and improves the conductive efficiency and corrosion resistance of the electrode.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic electrodes and relates to a method for forming a platinum group noble metal catalytic layer on the surface of a nickel textile mesh. Background Art
[0002] For the technology of hydrogen production by water electrolysis, in practical applications, the catalytic electrode is not only required to have good hydrogen evolution activity, but also to have good structural and performance stability. Supported noble metal catalyst is a commonly used catalyst, and its basic structure is to load noble metals (such as platinum, palladium, rhodium, etc.) on a carrier. Supported noble metal catalysts have many advantages, such as high activity, good selectivity, and low cost.
[0003] Since precious metals are expensive, loading them on low-cost carriers can effectively reduce the cost of catalysts. Therefore, they are widely used in many fields, such as petrochemicals, fuel cells, hydrogen-powered vehicles and other energy fields.
[0004] In the process of precious metal loading, it is often difficult to achieve uniform dispersion, and clusters or uneven particle structures are easily formed, which may lead to uneven distribution of active sites in the catalytic reaction and affect the overall performance of the catalyst. At the same time, the interaction between the carrier and the precious metal may lead to the deactivation or reduction of the precious metal active sites. It is particularly noteworthy that precious metal catalysts may face stability challenges during long-term use because the precious metals may dissolve into the electrolyte, thereby reducing the performance of the catalyst. Summary of the invention
[0005] The purpose of the present invention is to provide a method for forming a platinum group noble metal catalytic layer on the surface of a nickel woven mesh. The platinum group noble metal catalytic layer prepared by the present invention has strong stability and adhesion.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for forming a platinum group noble metal catalytic layer on the surface of a nickel textile mesh comprises the following preparation steps:
[0008] S1. Prepare a mixed alkali solution with deionized water, sodium hydroxide, sodium silicate and sodium carbonate, place the nickel textile mesh in the mixed alkali solution and ultrasonically clean it for 15-20 minutes, then ultrasonically clean it with deionized water and anhydrous ethanol for 15-20 minutes in sequence, and after drying, place the nickel textile mesh in a hydrochloric acid solution with a mass fraction of 10-15% and ultrasonically clean it for 10-20 minutes, and then ultrasonically clean it with deionized water for 10-20 minutes, wherein the concentration of sodium hydroxide in the mixed alkali solution is 5g / mL, the concentration of sodium silicate is 30g / mL, and the concentration of sodium carbonate is 15g / mL;
[0009] S2, placing the nickel textile mesh after step S1 in a conversion solution made of 0.2-0.5 g / L calcium alginate, 0.03-0.05 g / L calcium chloride and 0.5-1.0 g / L polyaspartic acid at room temperature, wherein the solid-liquid ratio of the nickel textile mesh to the conversion solution is 1:20 g / mL, adjusting the pH of the conversion solution to 4.0-4.2 with 0.1 mol / L ammonia water, the immersion time is 25-40 min, and after taking out, quickly rinse with deionized water, and dry at 100° C. for 5-8 h to obtain a pretreated nickel textile mesh;
[0010] S3, dissolving dopamine in a Tris-HCl buffer with a molar concentration of 10 mM to prepare a mixed solution with a mass concentration of 2-3 mg / L, adjusting the pH of the mixed solution to 8.5 with a 30% ammonia solution, stirring at room temperature for 20-24 hours, and mixing the obtained polydopamine with an ammonium salt after drying, wherein the mass ratio of polydopamine to ammonium salt is 1:0.8, heat-treating at 800-1100° C. for 4-7 hours under an inert gas atmosphere, cooling naturally to room temperature, and then pulverizing to obtain a solid powder;
[0011] S4, mixing the platinum group noble metal with the solid powder prepared in step S3, and preparing a solid powder of the platinum group noble metal through a mechanical alloying process;
[0012] S5. Spray the solid powder of the platinum group noble metal obtained in step S4 onto the surface of the pretreated nickel textile mesh by plasma spraying to obtain a nickel textile mesh having a platinum group noble metal catalytic layer formed on the surface.
[0013] As a preferred technical solution of the present invention, in step S3, the ammonium salt is at least one of ammonium bisulfate and ammonium sulfate.
[0014] As a preferred technical solution of the present invention, in step S4, the mass ratio of the platinum group noble metal to the solid powder prepared in step S3 is (60-80):(2-4).
[0015] As a preferred technical solution of the present invention, in step S4, the solid process of solid-state alloying of the mechanical alloying process is to put the platinum group noble metal and the solid powder prepared in step S3 into a ball mill and mill them at a speed of 600 r / min for 2 to 4 hours.
[0016] As a preferred technical solution of the present invention, in step S4, the platinum group noble metal is one or more of platinum, palladium and iridium.
[0017] As a preferred technical solution of the present invention, in step S5, the gases used in the plasma spraying are nitrogen and hydrogen, the pressure is 0.5~0.6Mpa, the nitrogen flow rate is 30~40L / min, the hydrogen flow rate is 5 L / min, the powder feeding rate is 40g / min, and the spraying distance is 100~120mm.
[0018] The invention first pre-treats the nickel textile mesh, and then removes organic oil stains on the surface of the nickel textile mesh by ultrasonic cleaning with a mixed alkali solution, wherein the mixed alkali solution is prepared from sodium silicate, sodium hydroxide and sodium carbonate, and the micelle structure generated by hydrolysis of the sodium silicate can effectively suspend solid dirt, and the sodium carbonate can remove insoluble impurities; then, ultrasonic cleaning is performed in deionized water and anhydrous ethanol to remove the alkali solution, and ultrasonic cleaning is performed in a hydrochloric acid solution to remove oxide impurities on the surface of the nickel textile mesh, thereby activating the surface of the nickel textile mesh for subsequent treatment.
[0019] The activated nickel textile mesh is placed in the conversion solution prepared by calcium alginate and polyaspartic acid. After immersion treatment, a polymer film is generated on the surface of the nickel textile mesh. On the one hand, polyaspartic acid and calcium alginate both have good water solubility. By mixing calcium alginate and polyaspartic acid, calcium alginate has good adhesion. At the same time, sodium alginate and polyaspartic acid form a more stable structure through cross-linking, which improves the adhesion of the film to the nickel textile mesh and the stability of polyaspartic acid, thereby helping polyaspartic acid to better form a uniform film on the surface of the nickel mesh, which can enhance the bonding force between the catalytic layer and the nickel textile mesh, thereby preventing The catalytic layer falls off during the electrolysis of water, improving the dispersibility of the catalyst and the stability of the catalytic layer. The roughness and pore structure of the surface of the nickel textile mesh can be changed by treating the surface film, increasing the specific surface area, and providing more attachment points and reaction active sites for the loading of the catalytic layer, thereby improving the loading efficiency and catalytic performance of the catalytic layer. In addition, the presence of the polyaspartic acid-calcium alginate film can change the charge distribution and wettability of the surface of the nickel textile mesh, which is conducive to the uniform distribution and stable attachment of the catalyst layer on the nickel textile mesh, protecting the catalyst particles to a certain extent, preventing them from falling off or aggregating during the loading process, and further improving the stability of the catalytic layer. At the same time, calcium alginate itself has certain adsorption properties, which can adsorb and fix the active components in the catalytic layer. This adsorption effect helps the uniform distribution of the catalytic layer on the surface of the nickel textile mesh.
[0020] On the other hand, both polyaspartic acid and calcium alginate have anti-corrosion properties, and their film layers can isolate the nickel textile mesh from direct contact with the corrosive medium to a certain extent, thereby slowing down the corrosion rate of the nickel textile mesh, reducing the dissolution and loss of the electrode during the electrolysis process, maintaining the shape and size of the electrode stable, and improving the reliability and efficiency of the electrolysis process. Thereby improving the corrosion resistance of the catalytic layer, avoiding the corrosion of the catalytic layer leading to a decrease in catalytic performance, and thus extending the service life of the electrode. In addition, polyaspartic acid has good electrical conductivity, which can improve the electrical conductivity efficiency of the electrode, reduce resistance, and thus promote the electrolysis reaction.
[0021] In the present invention, polydopamine and ammonium salt are pyrolyzed at high temperature. During the pyrolysis and carbonization process, sulfur dioxide or other sulfur-containing intermediates generated by the decomposition of ammonium sulfate or ammonium bisulfate will react with the carbon-nitrogen skeleton. In these reactions, sulfur atoms will replace hydrogen atoms or oxygen atoms in the carbon-nitrogen skeleton or undergo addition reactions with unsaturated bonds (such as double bonds or triple bonds) on the carbon-nitrogen skeleton, thereby obtaining sulfur-doped carbon-nitrogen compounds. The electronegativity of sulfur atoms is relatively high, and their introduction will change the electronic structure of the carbon-nitrogen compound, affecting the charge distribution and spin density, thereby enhancing the conductivity and catalytic activity of the catalyst layer. In addition, more defects and active sites can be generated on the carbon-nitrogen skeleton through sulfur modification, which are conducive to the adsorption and activation of reactants, and help improve the efficiency of the catalyst layer in the catalytic reaction.
[0022] Sulfur-modified carbon nitrogen powder is mixed as an additive with solid particles of platinum group precious metals, and a catalytic layer is formed by plasma spraying. The sulfur-modified carbon nitrogen particles have anti-poisoning properties and can reduce the risk of catalyst deactivation due to poisoning (such as reduced activity due to reaction with toxic substances). The sulfur-modified carbon nitrogen particles can be used as carriers or additives to promote the uniform dispersion of platinum group precious metal nanoparticles and enhance the interaction between platinum group precious metal particles and the nickel textile mesh carrier, preventing the metal nanoparticles from agglomerating during the reaction, thereby maintaining the activity of the catalytic layer, improving the catalytic efficiency and extending the life of the catalytic layer.
[0023] Beneficial effects of the present invention:
[0024] In the present invention, the nickel textile mesh is pretreated, and the oil and impurities on the surface are removed by washing with a mixed alkali solution and an acid solution to achieve the purpose of activation, and the surface of the nickel textile mesh is wrapped with a polyaspartic acid-calcium alginate membrane structure to provide more active sites for the catalytic layer, improve the adhesion of the catalytic layer, and thus improve the stability of the catalytic layer. Then, sulfur-modified carbon nitrogen particles are mixed with solid particles of platinum group noble metals, and a catalytic layer is formed by plasma spraying, thereby promoting the uniform dispersion of platinum group noble metal nanoparticles, and the interaction between the active sites of the enhanced platinum group noble metal particles and the nickel textile mesh carrier is enhanced to enhance adhesion, effectively prevent the metal nanoparticles from agglomerating during the formation of the catalytic layer, thereby maintaining the activity of the catalytic layer, improving the catalytic efficiency and extending the life of the catalytic layer. DETAILED DESCRIPTION
[0025] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0026] In the following Examples 1-3 and Comparative Examples 1-4:
[0027] The mixed alkali solution used is prepared by deionized water, sodium hydroxide, sodium silicate and sodium carbonate, wherein the concentration of sodium hydroxide is 5g / mL, the concentration of sodium silicate is 30g / mL, the concentration of sodium carbonate is 15g / mL, and the size of the nickel textile mesh used is 10*10cm 2 ; In step S2, the solid-liquid ratio of the nickel textile mesh to the conversion solution is 1:20 g / mL;
[0028] Calcium alginate: purchased from Hebei Chuangzhiyuan Biotechnology Co., Ltd.;
[0029] Calcium chloride: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: C805758;
[0030] Polyaspartic acid: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: P875765;
[0031] Dopamine: purchased from Shanghai Zhenli Biotechnology Co., Ltd.;
[0032] Ammonium bisulfate: purchased from Shanghai Jizhi Biochemical Technology Co., Ltd., product number: A83460;
[0033] Ammonium sulfate: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: A801013;
[0034] Palladium: purchased from Hubei Hanwei Chemical Co., Ltd.;
[0035] Platinum: purchased from Suzhou Yaco Technology Co., Ltd., catalog number: B0369;
[0036] Iridium: purchased from Hubei Hanwei Chemical Co., Ltd.;
[0037] Nickel woven mesh: purchased from Kunshan Daipinghu Electronic Technology Co., Ltd.
[0038] Example 1
[0039] S1. Prepare a mixed alkali solution with deionized water, place the nickel textile mesh in the mixed alkali solution and ultrasonically clean it for 15 minutes, then ultrasonically clean it with deionized water and anhydrous ethanol for 15 minutes in sequence, and after drying, place the nickel textile mesh in a 10% hydrochloric acid solution and ultrasonically clean it for 10 minutes, and then ultrasonically clean it with deionized water for 10 minutes;
[0040] S2, placing the nickel textile mesh after step S1 in a conversion solution prepared by 0.2 g / L calcium alginate, 0.03 g / L calcium chloride and 0.5 g / L polyaspartic acid at room temperature, adjusting the pH of the conversion solution to 4.0 with 0.1 mol / L ammonia water, immersing for 25 min, taking out and quickly rinsing with deionized water, and drying at 100° C. for 5 h to obtain a pretreated nickel textile mesh;
[0041] S3, dissolving dopamine in a Tris-HCl buffer with a molar concentration of 10 mM to prepare a mixed solution with a mass concentration of 2 mg / L, adjusting the pH of the mixed solution to 8.5 with a 30% ammonia aqueous solution, stirring at room temperature for 20 h, and mixing the obtained polydopamine with ammonium bisulfate after drying, wherein the mass ratio of polydopamine to ammonium bisulfate is 1:0.8, heat-treating at 800°C for 4 h in an inert gas atmosphere, cooling naturally to room temperature, and then pulverizing to obtain a solid powder;
[0042] S4, mixing platinum with a mass ratio of 60:2 with the solid powder prepared in step S3, putting the mixture into a ball mill and milling at a speed of 600 r / min for 2 h to prepare a solid powder of platinum group noble metal;
[0043] S5. The solid powder of platinum group noble metals obtained in step S4 is sprayed on the surface of the pretreated nickel textile mesh by plasma spraying to obtain a nickel textile mesh with a platinum group noble metal catalytic layer formed on the surface, wherein the gases used in the plasma spraying are nitrogen and hydrogen, the pressure is 0.5 MPa, the nitrogen flow rate is 30 L / min, the hydrogen flow rate is 5 L / min, the powder feeding rate is 40 g / min, and the spraying distance is 100 mm.
[0044] Example 2
[0045] S1. Prepare a mixed alkali solution with deionized water, place the nickel textile mesh in the mixed alkali solution and ultrasonically clean it for 17 minutes, then ultrasonically clean it with deionized water and anhydrous ethanol for 17 minutes in sequence, and after drying, place the nickel textile mesh in a 13% hydrochloric acid solution and ultrasonically clean it for 15 minutes, and then ultrasonically clean it with deionized water for 15 minutes;
[0046] S2, placing the nickel textile mesh after step S1 in a conversion solution prepared by 0.4 g / L calcium alginate, 0.04 g / L calcium chloride and 0.8 g / L polyaspartic acid at room temperature, adjusting the pH of the conversion solution to 4.1 with 0.1 mol / L ammonia water, immersing for 33 min, taking out and quickly rinsing with deionized water, and drying at 100° C. for 7 h to obtain a pretreated nickel textile mesh;
[0047] S3, dissolving dopamine in a Tris-HCl buffer solution with a molar concentration of 10 mM to prepare a mixed solution with a mass concentration of 2.5 mg / L, adjusting the pH of the mixed solution to 8.5 with a 30% ammonia aqueous solution, stirring at room temperature for 22 hours, and mixing the obtained polydopamine with ammonium bisulfate after drying, wherein the mass ratio of polydopamine to ammonium bisulfate is 1:0.8, heat-treating at 950° C. for 6 hours under an inert gas atmosphere, cooling naturally to room temperature, and then pulverizing to obtain a solid powder;
[0048] S4, mixing the solid powder prepared in step S3 with palladium in a mass ratio of 70:3, putting the mixture into a ball mill and milling the mixture at a speed of 600 r / min for 3 h to prepare a solid powder of a platinum group noble metal;
[0049] S5. The solid powder of platinum group noble metals obtained in step S4 is sprayed on the surface of the pretreated nickel textile mesh by plasma spraying to obtain a nickel textile mesh with a platinum group noble metal catalytic layer formed on the surface, wherein the gases used in the plasma spraying are nitrogen and hydrogen, the pressure is 0.55 MPa, the nitrogen flow rate is 35 L / min, the hydrogen flow rate is 5 L / min, the powder feeding rate is 40 g / min, and the spraying distance is 110 mm.
[0050] Example 3
[0051] S1. Prepare a mixed alkali solution with deionized water, place the nickel textile mesh in the mixed alkali solution and ultrasonically clean it for 20 minutes, then ultrasonically clean it with deionized water and anhydrous ethanol for 20 minutes in sequence, and after drying, place the nickel textile mesh in a 15% hydrochloric acid solution and ultrasonically clean it for 20 minutes, and then ultrasonically clean it with deionized water for 20 minutes;
[0052] S2, placing the nickel textile mesh after step S1 in a conversion solution prepared by 0.5 g / L calcium alginate, 0.05 g / L calcium chloride and 1.0 g / L polyaspartic acid at room temperature, adjusting the pH of the conversion solution to 4.2 with 0.1 mol / L ammonia water, immersing for 40 min, taking out and quickly rinsing with deionized water, and drying at 100° C. for 8 h to obtain a pretreated nickel textile mesh;
[0053] S3, dissolving dopamine in a Tris-HCl buffer with a molar concentration of 10 mM to prepare a mixed solution with a mass concentration of 3 mg / L, adjusting the pH of the mixed solution to 8.5 with a 30% ammonia solution, stirring at room temperature for 24 hours, and mixing the obtained polydopamine with ammonium sulfate after drying, wherein the mass ratio of polydopamine to ammonium sulfate is 1:0.8, heat-treating at 1100° C. for 7 hours under an inert gas atmosphere, cooling naturally to room temperature, and then pulverizing to obtain a solid powder;
[0054] S4, mixing iridium with a mass ratio of 80:4 with the solid powder prepared in step S3, putting the mixture into a ball mill and milling at a speed of 600 r / min for 4 h to prepare a solid powder of a platinum group noble metal;
[0055] S5. The solid powder of platinum group noble metals obtained in step S4 is sprayed on the surface of the pretreated nickel textile mesh by plasma spraying to obtain a nickel textile mesh with a platinum group noble metal catalytic layer formed on the surface, wherein the gases used in the plasma spraying are nitrogen and hydrogen, the pressure is 0.6 MPa, the nitrogen flow rate is 40 L / min, the hydrogen flow rate is 5 L / min, the powder feeding rate is 40 g / min, and the spraying distance is 120 mm.
[0056] Comparative Example 1
[0057] The difference between Comparative Example 1 and Example 1 is that in step S2 of Comparative Example 1, only polyaspartic acid treatment is performed, and the other operations are the same.
[0058] Comparative Example 2
[0059] The difference between Comparative Example 2 and Example 1 is that the nickel woven mesh in Comparative Example 2 is not processed by step S2, and the other operations are the same.
[0060] Comparative Example 3
[0061] The difference between Comparative Example 3 and Example 1 is that in step S3 of Comparative Example 3, no ammonium salt (ammonium bisulfate) is added, and the remaining operations are the same.
[0062] Comparative Example 4
[0063] The difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, solid powder of platinum group noble metal is directly used without going through step S3, and the other operations are the same.
[0064] Performance Test:
[0065] 1. The electrodes prepared in Examples 1-3 and Comparative Examples 1-4 were used as working electrodes, saturated calomel electrode was used as reference electrode, carbon rod was used as counter electrode, 1 M KOH solution was used as electrolyte, and linear sweep voltammetry was used at 80°C at a current density of 200 mA / cm 2 and 400mA / cm 2 The following tests are performed:
[0066] 2. The bending test was carried out using the metal covering layer bonding strength test standard ASTM B571, where the size of the electrode used was 10*10cm 2 ;
[0067] 3. The electrodes prepared in Examples 1-3 and Comparative Examples 1-4 were used as working electrodes, saturated calomel electrode was used as reference electrode, carbon rod was used as counter electrode, 1 M KOH solution was used as electrolyte, and the full water splitting performance test was performed at 50°C. The linear sweep voltammetry method was used to test the current density at 1.6V. The test results are shown in the following table:
[0068]
[0069] According to the above data, when the current is the same, the overpotential and test voltage of Examples 1-3 are lower than those of Comparative Examples 1-4, and the current density is higher at the same voltage, indicating that the electrode electrolysis efficiency prepared by Examples 1-3 is higher, so Examples 1-3 have higher catalytic activity and better electrochemical performance. According to the bending test data, the amount of layer shedding in Examples 1-3 is significantly less than that in Comparative Examples 1-4, and the catalytic layer prepared by the present invention has stronger adhesion and is more stable.
[0070] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for forming a platinum group noble metal catalyst layer on the surface of a nickel woven mesh, characterized in that: The method comprises the following preparation steps: S1. Prepare a mixed alkali solution with deionized water, sodium hydroxide, sodium silicate and sodium carbonate, place the nickel textile mesh in the mixed alkali solution and ultrasonically clean it for 15-20 minutes, then ultrasonically clean it with deionized water and anhydrous ethanol for 15-20 minutes in sequence, and after drying, place the nickel textile mesh in a hydrochloric acid solution with a mass fraction of 10-15% and ultrasonically clean it for 10-20 minutes, and then ultrasonically clean it with deionized water for 10-20 minutes, wherein the concentration of sodium hydroxide in the mixed alkali solution is 5g / mL, the concentration of sodium silicate is 30g / mL, and the concentration of sodium carbonate is 15g / mL; S2, placing the nickel textile mesh after step S1 in a conversion solution prepared by 0.2-0.5 g / L calcium alginate, 0.03-0.05 g / L calcium chloride and 0.5-1.0 g / L polyaspartic acid at room temperature, wherein the solid-liquid ratio of the nickel textile mesh to the conversion solution is 1:20 g / mL, adjusting the pH of the conversion solution to 4.0-4.2 with 0.1 mol / L ammonia water, the immersion time is 25-40 min, and after taking out, quickly rinse with deionized water, and dry at 100° C. for 5-8 h to obtain a pretreated nickel textile mesh; S3, dissolving dopamine in a Tris-HCl buffer with a molar concentration of 10 mM to prepare a mixed solution with a mass concentration of 2-3 mg / L, adjusting the pH of the mixed solution to 8.5 with a 30% ammonia solution, stirring at room temperature for 20-24 hours, and mixing the obtained polydopamine with an ammonium salt after drying, wherein the mass ratio of polydopamine to ammonium salt is 1:0.8, heat-treating at 800-1100° C. for 4-7 hours under an inert gas atmosphere, cooling naturally to room temperature, and then pulverizing to obtain a solid powder, wherein the ammonium salt is at least one of ammonium hydrogen sulfate and ammonium sulfate; S4, mixing the platinum group noble metal with the solid powder prepared in step S3, and preparing a solid powder of the platinum group noble metal through a mechanical alloying process; S5. Spray the solid powder of the platinum group noble metal obtained in step S4 onto the surface of the pretreated nickel textile mesh by plasma spraying to obtain a nickel textile mesh having a platinum group noble metal catalytic layer formed on the surface.
2. The method for forming a platinum group noble metal catalytic layer on the surface of a nickel woven mesh according to claim 1, characterized in that: In step S4, the mass ratio of the platinum group noble metal to the solid powder prepared in step S3 is (60-80):(2-4).
3. The method for forming a platinum group noble metal catalytic layer on the surface of a nickel woven mesh according to claim 1, characterized in that: In step S4, the solid-state alloying process of the mechanical alloying process is to put the platinum group noble metal and the solid powder prepared in step S3 into a ball mill and mill them at a speed of 600 r / min for 2 to 4 hours.
4. The method for forming a platinum group noble metal catalytic layer on the surface of a nickel woven mesh according to claim 1, characterized in that: In step S4, the platinum group noble metal is one or more of platinum, palladium and iridium.
5. The method for forming a platinum group noble metal catalytic layer on the surface of a nickel woven mesh according to claim 1, characterized in that: In step S5, the gases used in the plasma spraying are nitrogen and hydrogen, the pressure is 0.5-0.6 MPa, the nitrogen flow rate is 30-40 L / min, the hydrogen flow rate is 5 L / min, the powder feeding rate is 40 g / min, and the spraying distance is 100-120 mm.
Citation Information
Patent Citations
Biodegradable composite hydrogel and a preparation method and application thereof
CN109627765A
Multimetallic composite particles and method for preparing the same
KR1020160052203A